2004
DOI: 10.1136/adc.2003.037010
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic nasal continuous positive airways pressure in newborns of 28-31 weeks gestation: multicentre randomised controlled clinical trial

Abstract: Background: The role of nasal continuous positive airways pressure (nCPAP) in the management of respiratory distress syndrome in preterm infants is not completely defined. Objective: To evaluate the benefits and risks of prophylactic nCPAP in infants of 28-31 weeks gestation. Design: Multicentre randomised controlled clinical trial. Setting: Seventeen Italian neonatal intensive care units. Patients: A total of 230 newborns of 28-31 weeks gestation, not intubated in the delivery room and without major malformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
3
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 26 publications
2
41
3
4
Order By: Relevance
“…1,2,[11][12][13][14][15][16][17] Specific interventions included strategies to avoid hypothermia; establishment of lung volume in the least-invasive manner; and supporting teamwork with checklists, briefings, and debriefings.…”
mentioning
confidence: 99%
“…1,2,[11][12][13][14][15][16][17] Specific interventions included strategies to avoid hypothermia; establishment of lung volume in the least-invasive manner; and supporting teamwork with checklists, briefings, and debriefings.…”
mentioning
confidence: 99%
“…38 Success with CPAP depended on the experience of the staff and gestational age of infants, especially infants <29 weeks. 38 Sandri et al 39 in a multicenter trial demonstrated no difference in BPD in infants between 28 and 31 weeks gestational age treated with prophylactic or rescue NCPAP. A major limitation of NCPAP is the need for intubation due to frequent apnea, bradycardia or desaturations in preterm infants.…”
Section: Noninvasive Ventilation Strategiesmentioning
confidence: 97%
“…Success depended on the gestational age of the infants and experience of care providers over time. While evaluating the benefits of prophylactic NCPAP in more mature preterm infants born between 28 and 31 weeks gestation in a multicenter randomized clinical trial, Sandri et al 23 showed no benefits of prophylactic NCPAP over rescue NCPAP initiated when the oxygen requirements increased to greater than 40%. Recently, use of portable devices, such as Neopuff Infant Resuscitator (Fisher & Paykel Healthcare Corporation Limited, Irvine, CA, USA) to deliver consistent positive end-expiratory pressure in the delivery room and during transport from the delivery room, is gaining popularity.…”
Section: Cpap Generatorsmentioning
confidence: 99%